The effect of quality of worklife, work motivation and employee engagement on employee performance - Fancha, Rizka Fathya; Hadiwijaya, Dudung; Muttaqijn, Muhammad Imam (International Journal Labs, 2024)
This study aims to analyze the effect of quality of worklife, work motivation and employee engagement on employee performance at PT. Cahaya Engineering Sukses Bekasi used as a case study. This research approach uses quantitative, a total sample obtained as many as 110 respondents with a population of 150. Data collection techniques with observation, documentation and questionnaires with random sampling techniques. Multiple linear regression analysis methods with SPSS programs are used to analyze the data. The results showed that Quality Of Worklife had a positive but not significant effect while Work Motivation and Employee Engagement had a positive and significant effect on Employee Performance with Work Motivation variables that had a more dominant effect. Quality Of Worklife, Work Motivation and Employee Engagement simultaneously have a positive and significant effect on the performance of PT. Cahaya Engineering Sukses Bekasi. This shows that companies should focus more on improving Quality of Worklife and Employee Engagement in order to produce better employee performance.